FEATURES OF PLANTS’ DEVELOPMENT OF DIFFERENT SORTS OF WINTER WHEAT DURING THE AUTUMN GROWING SEASON, DEPENDING ON THE PRE-SOWING TREATMENT IN THE CONDITIONS OF NORTHERN STEPPE - Козельський, О. М. (Scientific Progress & Innovations, 2015)
The results of the survey indicate that the effectiveness of pre-sowing treatment of winter wheat by disinfectants and microfertilizer during it’s cultivation on the fallow, after pea and sunflower was high. Seed pre-treatment preparation of «Celest Top» 312.5 FS (1,5 l/t), which was used in full and reduced dose, together with microfertilizer «Reakom-plus-grain» contributed to a more rapid emergence of the plants of winter wheat. At the time of termination of autumn vegetation maximum values of the coefficient of tillering were observed on these experimental variants. Compared with control, the difference in tillering sorts Pysanka, Skarbnytsia and Apogej Luganskiy during it’s cultivation on a fallow was 15,4; 14,8; 16,0 % after pea and sunflower – 17,0; 17,4; 19,6 % and 18,6; 18,6; 19,5 % respectively. Germination and weight of 100 absolutely dry plants were also highest in these cases of the experience. On average for the years of research the highest yield of pre-sowing seed was provided by disinfectants «Celest Top» 312.5 FS (1,5 l/t) and microfertilizer «Reakom-plus-grain». During cultivation on fallow of sort Pysanka it was 6,40 tons per ha, of sort Skarbnytsia – 6,69 tons per ha, of sort Apogej Luganskiy – 6,20 tons per ha. Placing these sorts after sunflower and pea grain yield was 3,74; 3,50; 3,42 tons per ha and 4,43; 4,13; 3,94 tons per ha respectively.